Applications of the Stellar Spectrograph of the University of Athens Observatory - Gazeas, K. D.; Papathanassoglou, D. A. (9th International Conference of the Hellenic Astronomical Society, 2010)
The high quality stellar spectra, recorded with the stellar spectrograph constructed at the Laboratory of Astronomy and Applied Optics of the University of Athens, allows the spectral classification of stars brighter than 9 mag, as well as the measurement of radial velocities of binary systems. The primary application of the spectrograph will be the study of eclipsing binaries, where the lack of spectroscopic observations limits the theoretical models. The spectrograph can be also used for observations of transient phenomena, such as novae, supernovae, comets and cataclysmic variable stars, but also for support observations of larger telescopes around the world.